Compared cytogenetic of Drosophila starmeri (Diptera: Drosophilidae) of two Colombian isolated arid ecosystems - PRADA-Q., CARLOS FERNANDO; E. DE POLANCO, MA. MAGDALENA; ORDÓÑEZ-V., MARINA (Revista Colombiana de Entomología, 2003)
The phylogenetic route of Drosophila starmeri (Wasserman, Koepfer & Ward). chromosome 2, was established from two populations in the Colombian North Coast (Camarones and Santa Marta) and from a third one located in the Tatacoa desert (Rosalía). The latter was separated from the first two populations by more than 1.200 kilometers. The phylogenesis is summarized in the map, that was made using the method of the overlapped inversions and the techniques of chromosomal microphotography and scanner digitization. According to the results, the standard arrangement of the Drosophila starmeri chromosome 2 stems from the Drosophila martensis standard for four overlapped inversions. This chromosome shows polymorphism in three different arrangements. In this paper. we propose a new phylogenetic for chromosome 2. The results could be interpreted as a reflection of the genetic divergence between the populations of the North Coast and the Tatacoa. with a presumed interruption of the genetic flow. This divergence begins to be observed through the morphological and reproductive isolation studies done on the same populations, by groups researching cytogenetic, phylogeny and populations evolution, from the Universities of Tolima and Andes.